PENGARUH EDUKASI KESEHATAN DENGAN GROUP WHATSAPP TERHADAP PENGETAHUAN MENGENAI PENCEGAHAN STUNTING PADA SISWA SMAN 7 SAMARINDA - Intan Primadana; Dwi Hendriani, Nino Adib Chifdillah (ADISAM PUBLISHER, 2025)
Introduction: Stunting is a chronic condition that describes the inhibition of child growth. a report from the WHO World Health Organization, the prevalence of stunting in children in 2020 states that stunting toddlers in the world are the second highest in Southeast Asia reaching 31.8%. The 2021 Indonesian Toddler Nutrition Status (SSGI) stunting rate in Indonesia is 24.4%. The purpose of this study was to analyze the effect of health education with whatsapp groups on knowledge and attitudes regarding the prevention of stunting in students of SMAN 7 Samarinda Method: This research is a Pre-Experimental research with One group pretest-pos test design. The population in the study of class XII students amounted to 84 out of 282 people using proportional random sampling technique in sampling. Data analysis using Wilcoxon test. Results: The results of bivariate analysis showed that there was an influence before and after being given health education using whatssap media. There was an increase in knowledge from 34.5 to 64.3 and attitudes also increased from 28.2 to 69.0 the results of the Wilcoxon statistical test on knowledge and attitude variables were p = 0.00. Conclusion: There is an effect of health education using whatassap group on increasing knowledge and attitude in students of SMAN 7 Samarinda. It is expected that adolescents increase awareness regarding the importance of prevention of stunting. Suggestion: It is hoped that it can be the basis of science, especially in the health sector to conduct health education